Differentiate :-
1] exloga​ +ealoga+ealogx

2] elog (logx)​ .log3x

since eloga=a
1.
the given function is
y=ex.loga+ealoga+ealogxy=elogax+elogaa+elogxay=ax+aa+xa .......(1)differentiating eq(1) wrt x:dydx=ddx.(ax)+ddx.(aa)+ddx.(xa)  [let ax=tx.loga=logtloga=1t.dtdxdtdx=t.logadydx=ax.loga+0+a.xa-1=ax.loga+a.xa-1              


2.
the given function is


y=elog(logx).log3x i.e.y=(logx).(log3x) [which is product of two functionsdydx=(logx).ddx.(log3x)+[ddx(logx)][log3x]=(logx).13x.3+1x.log3x=logxx+log3xx=logx+log3xx=log(x.3x)x=log(3x2)x

hope this helps you

  • 5
What are you looking for?